2018
DOI: 10.7150/ijms.28452
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Geometrical Structure of a Honeycomb TCP on Relationship between Bone / Cartilage Formation and Angiogenesis

Abstract: A number of biomaterials have been developed, some of which already enjoy widespread clinic use. We have devised a new honeycomb tricalcium phosphate (TCP) containing through-and-through holes of various diameters to control cartilage and bone formation. However, the way in which the geometric structure of the honeycomb TCP controls cartilage and bone tissue formation separately remains unknown. In addition, an association has been reported between bone formation and angiogenesis. Therefore, in the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
(24 reference statements)
1
8
0
Order By: Relevance
“…We have confirmed that honeycomb β-TCP, in which linear through-holes with pore diameters of 300 µm are arranged in a honeycomb shape, has very high osteoinductive ability [18]. We also reported that this honeycomb β-TCP, which can reproduce the microenvironment, can control cell differentiation by changing the geometrical structure and enable differentiation of chondrocytes and osteoblasts [19]. Moreover, when we used a rat zygomatic defect model and implanted honeycomb β-TCP into the cheekbone defect, we obtained good bone fusion with the zygomatic stump bone.…”
Section: Introductionsupporting
confidence: 65%
“…We have confirmed that honeycomb β-TCP, in which linear through-holes with pore diameters of 300 µm are arranged in a honeycomb shape, has very high osteoinductive ability [18]. We also reported that this honeycomb β-TCP, which can reproduce the microenvironment, can control cell differentiation by changing the geometrical structure and enable differentiation of chondrocytes and osteoblasts [19]. Moreover, when we used a rat zygomatic defect model and implanted honeycomb β-TCP into the cheekbone defect, we obtained good bone fusion with the zygomatic stump bone.…”
Section: Introductionsupporting
confidence: 65%
“…In addition, by changing the pore diameter of honeycomb TCP, we have reproduced the hard tissue formation microenvironment and succeeded in specifically inducing and forming cartilage. Specifically, cartilage formation was observed in honeycomb TCP with a 75-μm pore size in rat femoral muscle [ 24 ]. Therefore, this honeycomb β-TCP, which can reproduce the microenvironment, can control cell differentiation by changing the geometrical structure and enabling differentiation of chondrocytes and osteoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they had a polar arrangement and exhibited odontoblast-like structures as if they were found in the pulp cavity. In our previous study, the angiogenesis regulated by the pore size of honeycomb TCP influenced on hard tissue formation [ 14 ]. The previous study indicated that the invasive blood vessel formation pattern in 300TCP which showed capillary pattern was different from that in 500TCP, which showed the same linear angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we reported that the surface properties resulting from the different sintering temperature affect the osteoinductivity and biocompatibility of TCP [ 13 ]. Furthermore, changing the through-holes diameters of honeycomb TCP holes allows for successful control of cartilage and bone formation [ 14 ]. In particular, in the skull defect model rat, vigorous bone tissue formation was observed in honeycomb TCP containing through-and-through holes with diameters of 300 μm, suggesting its clinical applicability [ 15 ].…”
Section: Introductionmentioning
confidence: 99%